The echoes of John Keats’ poetry in Preraphaelites’ artworks - Piotrowska, Agata Anna (Fundacja Pro Scientia Publica, 2018)
Aim of research and method. I have chosen to analyze two poems by John Keats, Isabella or the pot of basiland The Eve of St. Agnes, as well as four paintings trying to tell the same story in the pictorial way (these are Isabella and the pot of basil and The Eve of St. Agnes by J. E. Millais and two others by W. H. Hunt : Isabella and the pot of basil and The Eve of St. Agnes). The paper contain then an analysis of the iconography and the symbolism of the abovementioned paintings.The diversity of their relations with the literary prototype by Keats resulted in the devision of Preraphaelites’ works into portraits traying to highlight feelings of an individual and into narrative scenes attempting to tell the whole story in one single picture. Results. An analysis carried out in the paper has shown that both Millais and Hunt tried different approches to Keats’ poetry. They both created very synthetic illustrations to the poems, as well as portrayals of the individuals. Conclusions. The main conclusion is the observation that there existed very different approches to Keats’ poetry in the Preraphaelites’ paintings, all of which constituted quite volitional modifications of poet’s message. Painters were inspired by the abovementioned poems and many others, willing to create artworks equal to them, but in many cases they were seeing Keats only as an esthete, and thus they were just trivializing his poetry. Key words : Preraphaelites, Keats, romantic poetry, British painting, Millais, Hunt Wprowadzenie Poezja Keatsa, w szczególności niektóre spośród jego poematów, wywarły głęboki wpływ na twórczość wielu artystów różnych dziedzin, współczesnych poecie oraz późniejszych. Szczególne oddziaływanie tej poezji zaznaczyło się w malarstwie kręgu Prerafaelitów. Można by zadać sobie pytanie, jaki charakter miało to oddziaływanie: czy było to, jak chcieli sami Prerafaelici, oddziaływanie na zasadzie horacjańskiego ut pictura poesis, sugerującego równowartość i paralelizm malarstwa i poezji, mających wzajemne się dopełniać, czy ...